2015
DOI: 10.17221/61/2013-rae
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of selected properties of briquettes from recovered paper and board

Abstract: Brožek M. (2015): Evaluation of selected properties of briquettes from recovered paper and board. Res. Agr. Eng., 61: 66-71.Worldwide increasing energy demand is today permanently covered by a majority of non-renewable energy sources, namely by coal, crude oil and natural gas. This causes the rapid decline of their reserves and the time gets near when they will be run out. Therefore in the last years the exploitation of renewable energy sources has been permanently preferred. One of alternative fuel forms is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Thus, it can be concluded that fibrous materials have significant potential for bio-briquette production. In addition, the overall evaluation of both tested materials proved satisfactory when compared with other published data [72][73][74].…”
Section: Mechanical Analysis Of Briquette Samplessupporting
confidence: 54%
“…Thus, it can be concluded that fibrous materials have significant potential for bio-briquette production. In addition, the overall evaluation of both tested materials proved satisfactory when compared with other published data [72][73][74].…”
Section: Mechanical Analysis Of Briquette Samplessupporting
confidence: 54%
“…Previously published researches proved σ of bio-briquette fuel from bamboo fibre and sugarcane skin to be equal to 143.3 N∙mm -1 and 46.5 N∙mm -1 , respectively (Brunerová et al, 2018). Other studies proved the following results of σ bio-briquette fuel produced from different WB: “Jatoba” ( Hymenaea courbaril ) tropical hardwood - 47.05 3 N∙mm -1 (Chiteculo et al, 2018); empty poppy pods – 58.73 N∙mm -1 ; wheat husk – 44.18 N∙mm -1 (Brunerová et al, 2017a); plane tree chips – 176.1 N∙mm -1 (Brožek, 2016); waste paper – 32 N∙mm -1 ; and waste cardboard – 153 N∙mm -1 (Brožek, 2015). It is notable, that the observed level of σ (150.82 N∙mm -1 for bagasse bio-briquettes) occurs at a high level, thus, it can be positively evaluated as a successful result which proves the high mechanical quality of sugarcane bagasse bio-briquette fuel.…”
Section: Resultsmentioning
confidence: 99%
“…from wood waste (chips, shavings, sawdust, dust, bark), straw, coal, paper, cellulose, tobacco etc. are mostly utilized energetically (by combustion) (Basore, 1929;Punko and Gavrilovich, 2009;Plíštil et al, 2004;Brožek et al, 2012;Sheridan and Berte, 1959;Brožek, 2015a;2015b). After its compression the waste from combustible materials, e.g.…”
Section: Introductionmentioning
confidence: 99%